Shieldin – the protector of DNA ends - Setiaputra, Dheva (EMBO Rep, 2019)
DNA double‐strand breaks are a threat to genome integrity and cell viability. The nucleolytic processing of broken DNA ends plays a central role in dictating the repair processes that will mend these lesions. Usually, DNA end resection promotes repair by homologous recombination, whereas minimally processed ends are repaired by non‐homologous end joining. Important in this process is the chromatin‐binding protein 53BP1, which inhibits DNA end resection. How 53BP1 shields DNA ends from nucleases has been an enduring mystery. The recent discovery of shieldin, a four‐subunit protein complex with single‐stranded DNA‐binding activity, illuminated a strong candidate for the ultimate effector of 53BP1‐dependent end protection. Shieldin consists of REV7, a known 53BP1‐pathway component, and three hitherto uncharacterized proteins: C20orf196 (SHLD1), FAM35A (SHLD2), and CTC‐534A2.2 (SHLD3). Shieldin promotes many 53BP1‐associated activities, such as the protection of DNA ends, non‐homologous end joining, and immunoglobulin class switching. This review summarizes the identification of shieldin and the various models of shieldin action and highlights some outstanding questions requiring answers to gain a full molecular understanding of shieldin function.